ANALISIS HARGA POKOK PRODUKSI DAN STRATEGI PENGEMBANGAN INDUSTRI PENGOLAHAN IKAN TERI NASI KERING DI PULAU PASARAN KECAMATAN TELUK BETUNG BARAT KOTA BANDAR LAMPUNG - Laisa, Dwinta Diana; Sayekti, Wuryaningsih Dwi; Nugraha, Adia (Jurnal Ilmu-Ilmu Agribisnis, 2013)
The purpose of this study is to analyse the main production cost of dried rice anchovy processing industryâs. This study was located in Pasaran Island, West Teluk Betung Sub-District, Bandar Lampung City. This study uses cencus method involves all of 38 dried rice anchovy cultivator, independent community, the Head of Proccesing and Marking of Fishery From Marine and Fishieries Department of Bandar Lampung and one ofÂ  the Indonesiaâs Bank Placeman.Â  The analysis method in this study were determination of the main production cost and SWOT analysis. The result of the main production cost in summer monsoon, Normal monsoon, and eastern monsoon respectively were Rp43.330,15, Rp34.269,58 and Rp31.180,36. The selling price was determined on the main production cost by cultivator, so that the industry got the profit. The priority strategies to develope this processing industry were, a) using modern technology adoption, b) concluding a worker training, c) concluding a business book to maximize capital uses. Keywords: dried rice anchovy, pasaran island, strategy priority, SWOT analysis, the main production cost